1989
DOI: 10.1007/bf01963452
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a rapid latex agglutination test for detection of group B streptococci in vaginal specimens

Abstract: A rapid latex agglutination test (Bactigen Group B Streptococcus Cervical Screen) for detection of group B streptococci in cervical-vaginal specimens was evaluated using two different slide systems, the traditional serologic slide and capillary action track (Trak) slide. Culture was used as reference method. A total of 344 cervical-vaginal specimens were tested. The group B streptococci carrier rate was found by culture to be 10.8%, 56.8% of these specimens being heavily colonized. The sensitivity and specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…per swab) women, presenting the sensitivity and specificity of 63 and 99.7 %, respectively (Kontnick & Edberg, 2002). In two other analogous studies, sensitivity and specificity were reported as 85.7 and 99.3 %, respectively, by Wald et al (1987) and 95.2 and 99.3 %, respectively, by Lotz-Nolan et al (1989). In both these studies, a different method of antigen extraction, viz.…”
Section: Discussionmentioning
confidence: 87%
“…per swab) women, presenting the sensitivity and specificity of 63 and 99.7 %, respectively (Kontnick & Edberg, 2002). In two other analogous studies, sensitivity and specificity were reported as 85.7 and 99.3 %, respectively, by Wald et al (1987) and 95.2 and 99.3 %, respectively, by Lotz-Nolan et al (1989). In both these studies, a different method of antigen extraction, viz.…”
Section: Discussionmentioning
confidence: 87%
“…The results reported here with LPA-enzyme extraction (Streptex) demonstrated a sensitivity and a specificity in a heavily colonized population of 63 and 99.7%, respectively, analogous to the values found by Wald et al (25) (sensitivity and specificity, 85.7 and 99.3%, respectively). Lotz-Nolan et al (21) found a sensitivity and a specificity of 95.2 and 99.3%, respectively. Both of these studies, done with micronitrous acid extraction, demonstrated a better sensitivity than that found here.…”
Section: Discussionmentioning
confidence: 95%
“…Alternatively, the results reported here may be more reflective of the actual clinical situation, taking into account variations in collection, transportation, etc. (the study by Lotz-Nolan et al [21] was not performed under clinical conditions). All three studies had very similar specificities, indicating very few problems with other microbes producing false-positive results.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations